The Problem of the Nature of the Science of Tafsir by Enes Büyük (İstanbul: Ensar Publications, 2019), 232 pages, ISBN: 9786057619501 - Samir Abdou (Atebe)
This article focuses on the intricate nature of the science of tafsir. It discusses the function of tafsir within the framework of identifying the principles of tafsir methodology and tafsir narrations. The book’s contribution to the science of tafsir is emphasized by underlining that it aims to provide essential details for understanding and addressing the subject and comparing classical and modern understandings of tafsir. In addition, the scientific value of tafsir and its relationship with other Islamic sciences is examined. The work primarily focuses on identifying and analyzing the discussions regarding the nature of tafsir within Islamic thought.